2017
DOI: 10.1007/s10461-017-1716-7
|View full text |Cite
|
Sign up to set email alerts
|

Daily Marijuana Use is Associated with Missed Clinic Appointments Among HIV-Infected Persons Engaged in HIV Care

Abstract: We assessed the association between marijuana use and retention in HIV care through a retrospective cohort study of patients engaged in care at a large HIV clinic in 2011 and 2012. Two different retention outcomes were assessed: not meeting the Institute of Medicine’s (IOM) retention definition (≥2 provider visits ≥90 days apart in a calendar year) and no-show visits. Any marijuana use and frequency of marijuana use were obtained from a substance use screening questionnaire administered at each clinic visit. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Two noteworthy etiological implications stemming from cyclically related pathways to optimal retention may underlie these associations. First, consistent with Social Action Theory and studies with adults (Kipp et al, 2017; Traeger et al, 2012), substance use and legal involvement could be present and even co-occurring in youth who are in stressful circumstances characterized by poverty and unsafe communities. Thus, these YLH may be already facing barriers to retention, and engaging in problem behavior, perhaps because of being exposed to such conditions, further limits their ability to attend to treatment demands.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Two noteworthy etiological implications stemming from cyclically related pathways to optimal retention may underlie these associations. First, consistent with Social Action Theory and studies with adults (Kipp et al, 2017; Traeger et al, 2012), substance use and legal involvement could be present and even co-occurring in youth who are in stressful circumstances characterized by poverty and unsafe communities. Thus, these YLH may be already facing barriers to retention, and engaging in problem behavior, perhaps because of being exposed to such conditions, further limits their ability to attend to treatment demands.…”
Section: Discussionmentioning
confidence: 83%
“…YLH are particularly challenged with missing medical appointments (Horberg et al, 2013). Whereas research has paid attention to this behavior among adults (Horberg et al, 2013; Kipp et al, 2017; Traeger, O’Cleirigh, Skeer, Mayer, & Safren, 2012; Zinski et al, 2015), less is known about youth retention. Specifically, few studies have examined youths’ clinic attendance and its possible correlates (Harper et al, 2013; Kahana et al, 2015; Kahana et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study investigated the impact of marijuana use on retention in HIV treatment engagement [27]. Participants consisted of 1549 HIV-infected individuals who were mostly White (51%) and male (75%), with a median age of 45 years.…”
Section: Resultsmentioning
confidence: 99%
“…Although there was no association between marijuana use and the IOM outcome, the findings indicated that any marijuana use was associated with a 37% chance of missing their next medical appointment (adjusted RR 1.37 [1.12, 1.69]) with the highest risk among those reporting marijuana use between seven-14 times per week (1.67 [1.30, 2.15]). Kipp and colleagues [27] concluded that daily marijuana use negatively impacts subsequent HIV medical appointment attendance.…”
Section: Resultsmentioning
confidence: 99%